2002
DOI: 10.1128/jvi.76.16.8472-8474.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Attenuation Exhibited by Molecularly Cloned Highly Passaged Chicken Anemia Virus Isolates

Abstract: Chimeric virus experiments indicated that the pathogenicity and monoclonal antibody reactivity differences between two molecularly cloned, highly passaged chicken anemia virus isolates could be attributed to the VP1 amino acid change at residue 89. The introduction of this change into a pathogenic cloned low-passage isolate was not sufficient to cause attenuation.Chicken anemia virus (CAV) has a circular, single-stranded 2.3-kb DNA genome contained within an icosahedral capsid, 25 nm in diameter (9), and is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 9 publications
0
37
1
Order By: Relevance
“…Although there is evidence in other viruses such as rabies virus (Flamand et al, 1984), chicken anaemia virus (Scott et al, 2001;Todd et al, 2002), Newcastle disease virus (Meulemans et al, 1987), dengue fever virus (Lim & Ng, 1999) and tickborne encephalitis virus (Holzmann et al, 1990) that virulence (and attenuation) can be correlated, at least partly, to loss or modification of neutralizing epitopes, this was not supported for IBDV in our study. A role for the variable region of VP2 in virulence has been suggested by some authors (van Loon et al, 2002;Brandt et al, 2001), but it has never been shown to be critical in the sense that the presence of basic residues in the cleavage site of the F protein of Newcastle disease virus are for pathogenicity (Collins et al, 1993).…”
Section: Discussioncontrasting
confidence: 52%
“…Although there is evidence in other viruses such as rabies virus (Flamand et al, 1984), chicken anaemia virus (Scott et al, 2001;Todd et al, 2002), Newcastle disease virus (Meulemans et al, 1987), dengue fever virus (Lim & Ng, 1999) and tickborne encephalitis virus (Holzmann et al, 1990) that virulence (and attenuation) can be correlated, at least partly, to loss or modification of neutralizing epitopes, this was not supported for IBDV in our study. A role for the variable region of VP2 in virulence has been suggested by some authors (van Loon et al, 2002;Brandt et al, 2001), but it has never been shown to be critical in the sense that the presence of basic residues in the cleavage site of the F protein of Newcastle disease virus are for pathogenicity (Collins et al, 1993).…”
Section: Discussioncontrasting
confidence: 52%
“…The subgroups were not designated, therefore, we have used the subgroup terms 1A/1B, 1C, and 2A-2E developed by Olvera et al [6]. The variable structural protein, Cap, is considered most important due to its potential association with pathogenicity [21,22]. Some previous reports suggested that PCV2b viruses might be more pathogenic than those of PCV2a [7,20,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of these amino acid substitutions on CAVs need to be tested in the future. Tood, Scott, Ball, Borghmans, and Adair () reported that five amino acid changes at positions 75I, 89T, 125L, 141L and 144E of VP1 can induce attenuation. Furthermore, a marker for virulence was located at the amino acid position 394 of VP1 (Yamaguchi et al., ).…”
Section: Discussionmentioning
confidence: 99%